A study on employee job performance among courier workers in Selangor - Hasif, Hashem (2020)
The purpose of the study was to identify the relationship between employee motivation, job satisfaction, work-life balance, job stress and training towards employee job performance among courier workers in Selangor. This study used quantitative research methods by using questionnaires to collect the data from the courier workers in Selangor. Data were analysed using the Statistical Package for Social Sciences (SPSS). The findings showed that the relationship of all independent variables is significantly related to job performance. The independent variables can explain 50.3 % of variance in job performance among courier workers in Selangor is explained by motivation, job satisfaction, work life balance, job stress and training. The most influencing independent variable towards job performance among courier workers is motivation, followed by work life balance and job satisfaction and job stress and training. Finally, the study suggests that the dangerous of the job, attitude of the customer and the wage rates offer by the courier company could be considered in analysing in the future research.